2007
DOI: 10.1016/j.bbr.2007.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of GABAergic neurons but not astrocytes induces recovery of sensorimotor function in the traumatically injured brain

Abstract: Embryonic stem (ES) cells have been investigated in many animal models of injury and disease. However, few studies have examined the ability of pre-differentiated ES cells to improve functional outcome following traumatic brain injury (TBI). The purpose of the present study was to compare the effect of murine ES cells that were pre-differentiated into GABAergic neurons or astrocytes on functional recovery following TBI. Neural and astrocyte induction was achieved by co-culturing ES cells on a bone marrow strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…These deficits and forelimb asymmetries did not fully recover over time. The deficits were similar to those previously reported after CCI of the caudal forelimb area of the SMC (Becerra, 2007;Hoane et al, 2007;Nishibe et al, 2010). The severity and extent of the deficits and asymmetrical forelimb use were also similar to those found using the same measures following electrolytic (Kozlowski et al, 1996) or focal ischemic lesions of the FL-SMC (Hsu and Jones, 2006), both of which result in significant post-lesion neuronal growth responses.…”
Section: Figsupporting
confidence: 76%
“…These deficits and forelimb asymmetries did not fully recover over time. The deficits were similar to those previously reported after CCI of the caudal forelimb area of the SMC (Becerra, 2007;Hoane et al, 2007;Nishibe et al, 2010). The severity and extent of the deficits and asymmetrical forelimb use were also similar to those found using the same measures following electrolytic (Kozlowski et al, 1996) or focal ischemic lesions of the FL-SMC (Hsu and Jones, 2006), both of which result in significant post-lesion neuronal growth responses.…”
Section: Figsupporting
confidence: 76%
“…42,45 Rats were pre-tested for baseline levels on the two days prior to surgery. On each test day, the rats were placed in an empty fish tank (50 cm · 25 cm · 30 cm) and allowed to explore for 120 sec.…”
Section: Motor Assessment: Forelimb Asymmetry Taskmentioning
confidence: 99%
“…This is probably influenced by changes in the time of transplantation and the number of transplanted cells 40 . In another study, the transplantation of ESCs pre-differentiated into neuronal and glial precursors resulted in great sensory and motor improvements, but no cognitive improvement 41 , whereas in a similar study with GABAergic neuron transplantation, a greater sensorimotor recovery was observed, which was not seen when astrocytes were transplanted 42 . In yet another study, Gao et al 43 showed that human fetal NSCs pre-differentiated into neurons and then implanted into the hippocampus of TBI animals, were able to differentiate into neurons 1-day after injury, and the animals showed cognitive improvement.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 94%